TWIST BAND NEAT HANDWRITING (Proceedings of International Conference on Special Education, 2015)
This project entitled “Low Neatness Level of Handwriting among the preschool Special Needs learners of learning difficulties at Raja Melewar Teacher Education Institute” is a project under the Creative and Innovative Programme. It is developed with the intention to solve the problem of low neatness level in handwriting among preschool learners with learning difficulties. 3 research questions which are addressed in this project are, what factors may cause low neatness level of handwriting, can the Twist-Band-NeatHandwriting(TBNH) method increase the level of handwriting neatness and how effective is the TBNH method. This project sees the involvement of 8 lecturers and 5 preschool learners with learning difficulties and qualitative research methods are adopted. Methods which are used in this project are, the first being the Ishikawa Graphic to find root causes of low neatness level of handwriting, next, the systematic Plan, Do, Check and Act flow(PDCA) and pro-contra table to develop the innovative product of TBNH and the third method is observation during field research in order to gauge the effectiveness of TBNH. 4 preschools are involved in the field research and observation. Based on the analysis and observation done, it has been identified that the 3 main causes of low neatness level of handwriting are incorrect way of holding pencil, not being focused during writing session and non-systematic training in writing. Through brainstorming and PDCA sessions and pro-contra table, the TBNH pencil and manual are developed. By using various types of elastic bands and guided by the TBNH manual, the 5 subjects are able to acquire the correct technique of holding a pencil and control the formation of handwriting with an increase of 93.8% in neatness. The use of TBNH has also shortened the time spent in learning to acquire neat handwriting. TBNH also has been proven to be an effective technique to increase handwriting neatness level as 23 out of the 25 preschool learners in the field research observation are able to correct and improve their handwriting neatness. Preschool teachers also agree that TBNH has also changed the learners’ perception toward writing. Learners like writing activity more after the exposure to TBNH. As a conclusion, TBNH is an effective innovation that can be used to increase handwriting quality level and which then assures effective communication. It is hoped that this innovation can be broadcast for the purpose of knowledge sharing.